Knowledge, attitude, and practice toward COVID-19 transmission, prevention, and self-quarantine management among public servants in selected locations of the Sidama region, Southern Ethiopia: a multicenter cross-sectional study - Yacob Abraham Borie; Tomas Yeheyis; Bedilu Deribe; Mohammed Ayalew; Yared Reta; Dawit Hoyiso; Wegene Jembere (Frontiers Media S.A., 2023)
BackgroundThe COVID-19 epidemic has put an enormous strain on the world's healthcare systems, lifestyles, and quality of life. Ethiopia attempted to meet the myriad needs of its people due to the COVID-19 epidemic and the government has demonstrated a strong commitment in order to lessen the epidemic's impact on the populace. Despite this fact, the population's compliance with measures was not as needed.ObjectivesTo assess knowledge, attitude, and practice regarding COVID-19 transmission, prevention, and self-quarantine management among public employees in selected locations of the Sidama Region, Southern Ethiopia, in 2020.MethodsAn institution-based cross-sectional study was conducted from 01 October to 30 October 2020, among 399 public servants in selected locations of the Sidama Region, Sothern Ethiopia. One-stage cluster sampling was used to randomly select 16 public service sector offices from the total 32 sector offices in the selected locations of the region. Simple random sampling was employed to select respondents following equal distribution of the samples to 16 sector offices. Data were collected using an adapted self-administered questionnaire. Data entered using EpiData version 3.1 and SPSS version 24 were used for statistical analysis. Descriptive statistics was used to compute frequencies, percentages, and means for independent and dependent variables.ResultOverall, 42.36% of respondents had good knowledge of COVID-19, while the remaining 57.64% had poor knowledge. The percentage of favorable attitudes toward COVID-19 prevention and control were 65.2, 54.4% of respondents had a good level of practice of COVID-19 preventive and control measures, and 52.4% of the respondents had a good level of knowledge regarding self-quarantine management.ConclusionThe level of knowledge, attitude, practice, and self-quarantine management in the area is insufficient for preventing and controlling the disease. Evidence-based awareness creation and law enforcement in the study areas and surroundings, with an emphasis on infection prevention and control (IPC) in the public sector and other public gathering areas, is recommended.